Biological activities of the methanolic extracts from two varieties of Dimocarpus longan seeds - Natungnuy, K.; Chareonsap, P. P.; Poeaim, S. (My University, 2018)
Dimocarpus longan belongs to Sapindaceae which two varieties are found in Thailand. In addition to commercial longan (D. longan ssp. longan var. longan), in the eastern part of Thailand found another type of flora longan called Thao (D. longan ssp. longan var. obtusus). The total phenolic content and various biological activities was investigated including antioxidant, antibacterial, anti-tyrosinase and cytotoxic activities of the methanolic extracts from two varieties of these longan seeds. The results showed that the most activity of Edor (var. longan) seed extract presented higher biological activities than Thao (var. obtusus) seed extract. The total phenolic content by Folin-Ciocalteu method related to antioxidant activity in DPPH, ABTS and FRAP assays. In antibacterial activity using disc diffusion method both varieties of extracts (5 mg/disc) inhibited Staphylococcus aureus, Micrococcus luteus and Bacillus subtilis. However, in anti-tyrosinase activity by the dopachrome method Thao revealed similar activity to the commercial longan cultivar Edor with 50% inhibitory concentration (IC 50 ) values of 504.73 and 527.04 µg/ml, respectively. In cytotoxic activity using MTT assay with L929 (Mouse fibroblast cell line), Thao seed extracts were non-cytotoxic activity and stimulated skin cell lines, while Edor showed low cytotoxic activity. Therefore, their bioactive compounds should be studied further for developing longan seed extracts to cosmetic and pharmaceutical products in the future.
Keywords: Anti-tyrosinase activity; Antibacterial activity; Antioxidant activity; Cytotoxic activity; Dimocarpus longan